Studi Pustaka Tentang Hubungan Budaya Organisasi Terhadap Kinerja Pegawai Sektor Publik - Rizati, Leony; Wahidatunisa, Yolanda; Seviani, Dea; Aryani, Ririn Dwi; Lianti, Putri (UNIVED PRESS, Universitas Dehasen Bengkulu, 2025)
mployee performance in the public sector is a crucial element in assessing the effectiveness of government policies and service programs. One of the internal factors influencing this performance is organizational culture. A strong organizational culture is believed to foster a positive work environment, increase employee loyalty, and encourage the achievement of optimal results. However, not all public agencies possess a supportive organizational culture. This study aims to analyze and show that organizational culture in public institutions has an influence on the good or bad performance of the employees produced. It employs a descriptive qualitative approach, utilizing library research as the primary method of data collection, followed by content analysis. The findings indicate that employee performance in public institutions is influenced by organizational culture. The study shows that the better the organizational culture, the better the performance of employees. Therefore, organizations should routinely review their adopted cultural values and provide training aimed at strengthening organizational culture and enhancing employee motivation.